A Pilot Observational Study Assessing Long-Term Changes in Clinical Parameters, Functional Capacity and Fall Risk of Patients With Chronic Renal Disease Scheduled for Hemodialysis - Zemp, Damiano D.; Giannini, Olivier; Quadri, Pierluigi; Tettamanti, Mauro; Berwert, Lorenzo; Lavorato, Soraya; Pianca, Silvio; Solcà, Curzio; de Bruin, Eling D. (Frontiers in Medicine, 2022)
Background Patients with end-stage renal disease are known to be particularly frail, and the cause is still widely seen as being directly related to specific factors in renal replacement therapy. However, a closer examination of the transitional phase from predialysis to long-term hemodialysis leads to controversial explanations, considering that the frailty process is already well-described in the early stages of renal insufficiency. This study aims to describe longitudinally and multifactorially changes in the period extending from the decision to start the replacement therapy through to the end of 2 years of hemodialysis. We hypothesized that frailty is pre-existent in the predialysis phase and does not worsen with the beginning of the replacement therapy. Between 2015 and 2018 we recruited 25 patients (72.3 ± 5.7 years old) in a predialysis program, with the expectation that replacement therapy would begin within the coming few months. Methods The patients underwent a baseline visit before starting hemodialysis, with 4 follow-up visits in the first 2 years of treatment. Health status, physical performance, cognitive functioning, hematology parameters, and adverse events were monitored during the study period. Results At baseline, our sample had a high variability with patients ranging from extremely frail to very fit. In the 14 participants that did not drop out of the study, out of 32 clinical and functional measures, a statistically significant worsening was only observed in the Short Physical Performance Battery (SPPB) score (p < 0.01, F = 8.50) and the number of comorbidities (p = 0.01, F = 3.94). A careful analysis, however, reveals a quite stable situation in the first year of replacement therapy, for both frail and fit participants and a deterioration in the second year that in frail participants could lead to death. Conclusion Our results should stimulate a reassessment about the role of a predialysis program in reducing complications during the transitional phase, but also about frailty prevention programs once hemodialysis has begun, for both frail and fit patients, to maintain satisfactory health status.